Cultivating underutilized vegetables in arid region - Samadia, Dilip Kumar (Indian Horticulture, 2019)
Dryland horticulture has immense significance in providing nutrition rich food, social security and eco-restoration to the inhabitants of desert and tribal areas of Rajasthan. While assessing distinctness of hot arid and semi-arid agro-climate (1994–1997), it is realized that non-availability of requisite crop–genotypes and production practices are two prime constraints in success of vegetable culture. Traditionally, kachri (Cucumis melo var. callosus / agrestis), kakadia / snap melon (Cucumis melo var. momordica), mateera (Citrullus lanatus), tinda (Praecitrullus fistulosus) and guar (Cyamopsis tetragonoloba) is grown with mixed cropping. Besides, khejri (Prosopis cineraria) is playing vital role in longestablished farming system, and its tender pods are used as vegetable. With the establishment of national centre in 1993 at Bikaner, systematic research work was started for germplasm conservation and utilization in native crop-plants having vegetable potentialities. There is a scope in getting quality marketable yield adopting production site management concept, provided trait specific genotypes. With khejri based models, higher yield in prioritized vegetables and income @ ` 75,000–2,25,000 ha/year is obtained compared to traditional cropping (` 23,000–42,000). Thus, technological advancement in under-exploited vegetables is a boon toward doubling farmer’s income in resource-poor arid environment.